CONSTRUCTION MANAGEMENT ANALYSIS OF CIDERES HOSPITAL - Zaid Al Hakim; Saihul Anwar (Journal of Green Science and Technology, 2019)
Reliable infrastructure requires effective and efficient management from the planning, structural, construction, operational and maintenance phases to the end of service life. Good management of civil infrastructure guarantees not only to save funds, but to use natural resources appropriately, thus ensuring ecological sustainability.Construction management is part of civil engineering science that focuses on managing construction projects to realize technical concepts and designs produced by other parts of civil engineering science. Construction management aims to build built physical facilities or infrastructure that is needed to support human life.Management of construction projects is becoming increasingly complex due to the many parties that interact in it and the increasingly high demands for quality of functions, comfort, security, aesthetics and sustainability. Therefore construction management is needed to ensure the efficiency and productivity of a construction project in meeting various expectations and requirements.This thesis analysis includes volume calculation, Needs of labor, materials and equipment, Bar chart, Cash flow, S Curve, method of CPM (Critical Path Method) is a method of identifying critical work paths or items. Forwards calculation, backwards calculation, free float and total float. Based on the calculation of cash flow to complete the construction of Cideres Hospital Kadipaten Dawuan Majalengka project until final stage more or less cost as much Rp. 9,034,000,000,00. These costs are divided into two parts, structure and architecture work ,for structures the cost as much Rp. 3,644,000,000,00 and for architecture the cost is Rp. 5,390,000,000,00. From the calculation of CPM scheduling analysis, the development of Cideres Hospitalproject takes time for 45 weeksKeyword: Project Management, Bar Chart, S Curve, Critical Path Method